Archetypes of youth as vectors in power relations - From praises to information operations - Meriläinen, Niina; Hiljanen, Mikko; Rautiainen, Matti (Frontiers in Political Science, 2023)
The purpose of this explorative and mixed methods research is to discover and describe the possible archetypes of high school and vocational school students from empirical data produced by young people and media, and to discuss what kinds of power relations these archetypes can create in Finnish society. Indeed, the empirical data produced by young people and those found in newspapers reveal archetypes and various power relations. In particular, the data indicate how the vectors of such archetypes guide thinking about young people and their life courses. In particular, the archetypes illustrate how vocational school students have to defend themselves and their choices in their daily lives, while high school students do not. Furthermore, the empirical data illustrate how the lives of vocational school students are mainly described as happening here and toward the future of the voiceless proletariat, while high school students are considered active and successful changemakers. Vocational school students also question official Finland and the place where they have been situated. Among others, this can create an opportunity for information operations.